Infraestrutura e produtividade: uma análise empírica - Mussolini, Caio Cesar (2007)
The main goal of this dissertation is to analyze the relationship between infrastructure and total factor productivity (TFP) in Brazil and other Latin America countries — Argentina, Chile and Mexico. At first, it was estimated the impact of the ratio of public capital-private capital over the Brazilian’s productivity. In that sense, it was used a VECM to investigate the interaction between these variables, whether on the long run, or the short (medium) run. In fact, it was found that this complementary relation (public-private) helps in explainning TFP’s path from 1950 to 2000. Besides, the short (medium) run analysis has indicated that (positive) shocks in this relation have a significant effect over the TFP, but the opposite is not true. After that, the hypothesis of cointegration between physical infrastructure measures (electricity energy, roads and telecomunnication) and TFP regarding those countries was tested, using two methodologies — the Johansen test and the Saikkonen and Lütkepohl test (S&L). The estimated elasticities suggest that the energy and the road sector have a positive influence over TFP, therefore, on the long run economic growth. The telecomunnication sector has not presented robust results of cointegration, which could indicate a less expressive effect of this sector over the long run growth.